Exploring Embodiment Through Choreographic Practice - Pickard, Angela (Frontiers in Psychology, 2018)
This pilot explores embodiment and gender representation through the lens of choreographic practice and sociology. The perspective derives from a comparative lack of status held by female (vs male) choreographers in the UK. The pilot study specifically addresses how choreography itself embodies and perpetuates sociocultural values. This work is part of a larger, on-going ethnographic study into the social world(s) of choreography and choreographers. The method is a process of dance making called Sonnet that would expose habitual expectations of dance performances. The process was designed to heighten awareness, nudge and challenge dancers and audience members to reflect on what they normally take for granted. Using Pierre Bourdieu’s critique and notion of habitus (embodiment), the study indicates perpetuating social hierarchy in dance training and practice. This is explored and framed from Bourdieu’s social and cultural perspective.